South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper describes South Africa's economic development and challenges. South Africa has made considerable economic and social progress over the past two decades, but faces substantial challenges. Global transitions-China's slowdown and rebalancing, weak commodity prices, and U.S. monetary policy normalization-are taking a heavy toll on South Africa. Growth and employment, which were already low, are faltering and continue to underperform peer countries. Vulnerabilities remain elevated and have increased in the real and fiscal sectors. Boosting growth and job creation, thus reducing extremely high unemployment and inequality, and promoting social transformation remain South Africa's key challenges.